Compound Nouns Found in The Jakarta Post Website - Octavianti, Erisa; Sutjiati Beratha, Ni Luh; Sukarini, Ni Wayan (Humanis, 2021)
This study is aimed to identify the types of compound nouns and analyze the meanings of compound nouns conveyed on The Jakarta Post website. Two theories applied in this study, the theory of compound proposed by Katamba and the theory of meaning proposed by Palmer. Eight articles from The Jakarta Post website were chosen as the data source. The selected articles are related to technology, lifestyle, and business from December 2020 until February 2021 . Documentation method and note-taking technique used in collecting the data. The collected data was analyzed by using a descriptive qualitative method and triangulation technique. Meanwhile, in presenting the data analysis, this study used formal and informal methods. The result shows that all types of compound nouns based on the theory applied are found in the data source. The types are: noun + noun, adjective + noun, and preposition + noun. In terms of meaning, there are transparent and opaque meanings.